Musculoskeletal Biomechanics - Brett Szymik; Jennifer Stowe (Association of American Medical Colleges, 2015)
Abstract This is a lecture/large-group session with a breakout small-group case discussion. This session was created as an introduction to the biomechanics of the human musculoskeletal system for first-year medical students. The purpose of the session is to introduce the basic concepts behind how the musculoskeletal system is constructed and how it produces movement. The session opens with a brief introduction to skeletal muscle, a discussion of forces and lever mechanics, then overview of torque production using qualitative and basic quantitative techniques. A section on the components of force vectors and the composition of multiple forces leads into two clinical examples, one of which can be used in conjunction with the provided handout for an in-class student breakout session. This session is specifically targeted at first-year medical students who are at the beginning of their course on the musculoskeletal system. This course is very anatomy intensive, and one of the objectives of this session is to empower first-year students to conceptualize the human musculoskeletal system as a series of levers, whereby muscles produce torque about freely movable joints. One goal of this resource is to help decrease the amount of memorization that students must perform by increasing their ability to describe specific movements and the joints/muscles involved in producing those movements. A large amount of anecdotal student feedback indicates that this session succeeds in changing students' perception of the musculoskeletal system from one of intense memorization towards one of increased understanding of movement. Students have historically performed well on assessment items mapped to the learning objectives of this session, and formal student feedback from this session historically has been incredibly positive.